Application of quantitative real-time PCR to detect Mink Circovirus in minks, foxes and raccoon dogs in northern China - Liu, Yingyu; Sheng, Chenyan; Zhou, Yu; Li, Jianming; Gong, Qinglong; Shi, Kun; Liu, Fei; Xu, Lihui; Cui, Zhenzhen; Leng, Xue; Du, Rui (Frontiers in Microbiology, 2023)
Mink circovirus disease caused by Mink Circovirus (MiCV) is a serious infectious disease of mink that has become prevalent in recent years in China, severely affecting the reproductive performance of mink and causing significant economic losses to farms. To date, there have been few studies on MiCV, its pathogenic mechanism is not clear, and there is no effective vaccine or drug to prevent and control the disease. Therefore, it is necessary to establish a rapid and reliable molecular diagnostic method, which would aid future studies of this novel virus. In our study, we developed a sensitive and specific TaqMan-based quantitative real-time PCR assay targeting the MiCV Cap gene. The assay showed no cross-reaction with other tested animal viruses. The assay is highly sensitive, with a detection limit of as low as 10 plasmid DNA copies and 2.38 × 10-2 pg of viral DNA. The intra and inter--assay coefficients of variation were both low. The positive detection rate of MiCV in clinical samples from minks, foxes, and raccoon dogs were 58.8% (133/226), 50.7% (72/142) and 42.2% (54/128), respectively, giving a total positive detection rate of 52.2% (259/496). Higher contamination levels were observed in samples from the environment in direct or indirect contact with animals, with a total positive detection rate of 75.1% (220/293). These epidemiological results showed that minks, foxes, and raccoon dogs had high infection rates of MiCV. This was aslo the first study to detect MiCV on the ground and equipment of fur-bearing animal farms. Our assay is highly sensitive and specific for the diagnosis and quantification of MiCV, and should provide a reliable real-time tool for epidemiological and pathogenetic study of MiCV infection.